Perception of bullying and management of conflict and climate in school officers and teachers schools - Quintana Peña, Alberto Loharte (2012)
In order to explore the relationship between management skills to negotiate conflicts, the perception of bullying and school organizational climate presented by principals and teachers of schools, was investigated for the estates management and teaching from six education. Data collection was done through three instruments: the Organizational Social Climate Questionnaire and two others that were specially adapted to our environment: the scale of perceived bullying teachers and administrators at Schools and Test Management Skills Negotiation in Conflict. Information was collected through a descriptive design and correlational, with a circumstantial non-probability sampling the study population. To quantify the results are applied the statistical nonparametric Kendall Tau to establish correlations between these variables. Finally, we conclude that when the organizational climate school principals shown autocratic presented higher prevalence of peer harassment in schools, whereas, when the school organizational climate has permanent network of friendship and support among teachers, will present a lower prevalence of peer harassment in schools.